Evaluation of chips formation of AISI 316L SS using precision end-milling - Yasir, M. (Asian Research Publishing Network, 2016)
This paper discusses in detail precision end-milling approach in order to study the chips morphology of AISI 316L stainless steel which affects the machinability to a greater extent. The cutting speed ranges of 80 to 140 m/min while the feed rate ranges from 0.025 mm/tooth to 0.04 mm/tooth were investigated. Scanning electron microscope (SEM) was used for the 3D-view analysis in order to study the top surface, length of chip, width, thickness of chips and shear bands of the chips. Experimental results conclude that the chip length increases with an increase in cutting speed (VC). Furthermore, the chip width decreases with an increase in feed rate (f). The chips become thicker as the cutting speed is increased. A relationship was built between the surface roughness and surface integrity with the chip morphology. Â© 2006-2016 Asian Research Publishing Network (ARPN).